RISK FACTORS AND CAUSES OF NEONATAL DEATHS IN NAMIBIA - Nelago Indongo (European Scientific Journal, ESJ, 2014)
Objectives Toidentify the common causes and risk factors of neonatal deaths in facilities in five regions in Namibia. Methods This descriptive study was carried out atall health facilities providingmaternity care services in the five regions, A total of 498 neonatal deaths recorded in each of the facilities during the period under study January 1, 2010–June 30, 2012 were reviewed. These deaths were evaluated for age, gestational age, birth weight, risk factors and cause of death. Results About 46.4% of neonates who died had a birth weight less than 1500g and most of them had a gestational age of 26-32 weeks (45.2%). The most common cause of neonatal death was prematurity (n=270 or 54). Respiratory distress syndrome (n=131), birth asphyxia (n=88), sepsis (n=86), and congenital malformations (n=50) were also prevalent causes of neonatal deaths. The third type of delay (delay in receiving care) was perceived to be common (47.8%) for neonatal death cases, reinforcing the fact that two-thirds of neonatal deaths occurred at the hospital where the woman laboured and delivered.The most common reason given for the delay was a lack of facilities (including medications and supplies) to care for premature neonates, lack of trained and available providers. Other causes of the third type of delay noted were delays transferring neonates to higher-level facilities and delays in making the decision to perform a Caesarean section during prolonged labour. Overall, 102 (23.1%) of neonatal deaths for whom maternal HIV status was indicated were born to HIVpositive mothers. Fifty-nine (11.8%) of these mothers were on full HAART during pregnancy; 31 (6.2%) mothers were on ARV prophylaxis and 62 (12.4%) neonates born to HIV-positive women received early ARV prophylaxis. Conclusion The mortality rate was high inlow birth weight neonates. Measures to prevent neonatal mortality must be exercised with emphasis on skilled attendance at birth and appropriate care of low birth weight neonates.